The basic solution ellipsoid method approach for the efficiency measurement problems - Laurinavičius, Eligijus; Rimkuvienė, Daiva; Sakalauskaitė, Aurelija (Lietuvos matematikos rinkinys, 2016)
The efficiency is a measure of a performance of a decision making units (DMUs can be a firm, a person, an organization). The data envelopment analysis (DEA) is a datadriven non-parametric approach for measuring the efficiency of a set of DMUs. The DEA is a linear programming (LP) based technique which deals with the basic models (CCR, BCC, SBM, additive) of the efficiency evaluation. This paper presents basic solution ellipsoid method approach associated with some problems of initial basic solution and the steps of it.
Keywords: efficiency; data envelopment analysis; linear programming; basic ellipsoid